MEDAN MAKNA VERBA MEMASAK DALAM BAHASA MELAYU DIALEK SAMBAS - rizki, Nurul; Simanjuntak, Hotma; Rasmawan, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the diversity of the meaning of cooking verbs in Sambas Dialect Malay Language. The subproblems in this study are, the meaning of cooking fields, components of cooking meanings, types of cooking lexical meanings, and text procedures related to cooking verbs in Indonesian language learning based on 2103 curriculum. While the benefits of this study as a form of regional language preservation. This research uses a descriptive method. In data collection the author uses skillful listening techniques, fishing techniques and recording and recording techniques. The technique of testing the validity of data uses peer review techniques through discussion and reference coverage. Based on the results of the study found 35 cooking lexemes. The cooking verb can be divided into several parts. Based on the water media there are 23 lexemes, the oil media has six lexemes, and the fire media has five lexemes. Based on the cooking process exposed to fire there are five lexemes and not exposed to fire, there are thirty lexemes. Based on tools for cooking using stoves or stoves, there are thirty lexemes and embers of fire, there are five lexemes.Keywords: Cooking verb, Sambas Dialect Malay Language